Optimization of Vitamin a Nutrition of Calves Fattened on Wastes of Food Industry - Vladimirovich Valoshin, Andrey; ., . (International Journal of Engineering and Technology, 2018)
The most important sources of fodder resources are wastes of food industry: pulp, distiller's grains, brewer's grains, malt sprouts, etc., which are widely used for cattle fattening.The research was aimed at determining the optimal dosages of vitamin A in the diet of calves fattened on pulp, distiller's grains, brewer's grains, and malt sprouts.Â Â